Neuronal correlates of social decision making are influenced by social value orientation—an fMRI study - Kuss, Katarina; Falk, Armin; Trautner, Peter; Montag, Christian; Weber, Bernd; Fliessbach, Klaus (Frontiers in Behavioral Neuroscience, 2015)
Our decisions often have consequences for other people. Hence, self-interest and other-regarding motives are traded off in many daily-life situations. Interindividually, people differ in their tendency to behave prosocial. These differences are captured by the concept of social value orientation (SVO), which assumes stable, trait-like tendencies to act selfish or prosocial. This study investigates group differences in prosocial decision making and addresses the question of whether prosocial individuals act intuitively and selfish individuals instead need to control egoistic impulses to behave prosocially. We address this question via the interpretation of neuronal and behavioral indicators. In the present fMRI-study participants were grouped into prosocial- and selfish participants. They made decisions in multiple modified Dictator-Games (DG) that addressed self- and other-regarding motives to a varying extent (self gain, non-costly social gain, mutual gain, costly social gain). Selfish participants reacted faster than prosocial participants in all conditions, except for decisions in the non-costly social condition, in which selfish participants displayed the longest decision times. In the total sample we found enhanced neural activity in the ventromedial prefrontal cortex (vmPFC) and dorsomedial prefrontal cortex (dmPFC/BA 9) during decisions that resulted in non-costly social benefits. These areas have been implicated in cognitive control processes and deliberative value integration. Decisively, these effects were stronger in the group of selfish individuals. We believe that selfish individuals require more explicit and deliberative processing during prosocial decisions. Our results are compatible with the assumption that prosocial decisions in prosocials are more intuitive, whereas they demand more active reflection in selfish individuals.